Берытскыны вуоз дыры: кылбуръёс / Михаил Федотов - Федотов Михаил Иванович (Удмуртия, 2018)
Экземпляры: (20201012) / Инвентарный номер: 41590 / Цена: 300.00 / Сис.шифр: 84(2=664.1) / Авт.знак: Ф 34 / ГРНТИ: 17.82 / ББК: 84(2=664.1)